Indian atrocities in Bollywood: A Critical appraisal of Conflict and Peace Journalism - Muhammad Tarique; Lubna Shaheen (Journal of Peace, Development and Communication, 2021)
Bollywood is the ever-growing Indian cinema industry that has converted into one of the major film productions in the world. Multifaceted topics make it popular among the Pakistani diaspora living all over the world. Kashmir is a chronic Indo Pak conflict that is subject to many Bollywood movies. These movies are far from ground truths as the United Nations and human rights organizations are providing an opposite picture, and accusing India of unremitting human rights violations in Indian occupied Kashmir. The cinematic stereotypical dualistic presentation creates distance and haters between both countries and causes perturbance among Muslim diaspora around the world. This research is based on the movies where such a binary has been depicted by selecting the two most popular movies on Kashmir.